2010
DOI: 10.1093/annonc/mdp398
|View full text |Cite
|
Sign up to set email alerts
|

Psychological distress among male patients and male spouses: what do oncologists need to know?

Abstract: Social support received by male cancer patients from friends and family may be mediated by spouse support. As a result, single male patients are at higher risk for psychological distress. Male spouses were also found to have high rates of distress. These two groups need special attention by oncologists.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
98
0
2

Year Published

2011
2011
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 136 publications
(106 citation statements)
references
References 28 publications
6
98
0
2
Order By: Relevance
“…Studies showed diagnosis of cancer caused more distress than other diseases 29. Married people were easier to benefit from social support from their friends and family and displayed less distress and depression after the cancer diagnosis 30. Patients with depression displayed three times greater odds to be noncompliant with medical treatment recommendations compared with those who were not depressed 31.…”
Section: Discussionmentioning
confidence: 99%
“…Studies showed diagnosis of cancer caused more distress than other diseases 29. Married people were easier to benefit from social support from their friends and family and displayed less distress and depression after the cancer diagnosis 30. Patients with depression displayed three times greater odds to be noncompliant with medical treatment recommendations compared with those who were not depressed 31.…”
Section: Discussionmentioning
confidence: 99%
“…32,33 In addition, our study showed that nonmarried patients experienced elevated mortality compared with married patients, an observation consistent with previous findings for many cancers including NHL. [34][35][36] The most likely explanation is that married patients have stronger social support from spouses, 34 which results in better adherence with prescribed treatments 37 and less psychological difficulties, 38 than nonmarried cancer patients. Our finding of the more marked inverse association between SES and mortality in married DLBCL patients may result from differences in insurance status between married and nonmarried DLBCL patients in our study.…”
Section: Discussionmentioning
confidence: 99%
“…27 Furthermore, as suggested by previous studies, the phenomenon can be further explained by the psychological factors in cancer development itself as well as compliance or adherence to cancer-related therapy. 27,[29][30][31][32] Therefore, the effect of marriage on patient survival is likely the result of interactions within a complex network of social-economic-psychological factors, and marital status maybe one of the best parameters to summarize this network. Our study also identified follicular lymphoma as a significant factor in prolonging survival in PISCL patients, with a relative hazard of 0.25 when compared with diffuse large B-cell lymphoma; in contrast, other cell types did not demonstrate a similar association.…”
Section: Neurooncologymentioning
confidence: 99%